2003
DOI: 10.1385/jmn:20:3:395
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Apolipoprotein E Expression in Response to Dietary and Pharmacological Modulation of Cholesterol

Abstract: Apolipoprotein E (ApoE) influences the risk of late onset Alzheimer's disease (AD) in an isoform-dependent manner, such that the presence of the apoE epsilon4 allele increases the risk of AD while the presence of the apoE epsilon2 allele appears to be protective. Although a number of ApoE functions are isoform dependent and may underlie the "risk factor" activity of AD, its ability to bind amyloid beta peptides and influence their clearance and/or deposition has gained strong experimental support. Evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 80 publications
4
44
1
Order By: Relevance
“…In rodents, elevated apoE levels correlate with impaired cognitive function (Kadish et al 2009). Increased apoE expression resulting from high dietary cholesterol in humans is also associated with an increased incidence of AD (Petanceska et al 2003). Nonhuman primates show an age-related decline in performance on tasks associated with PFC and hippocampal Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, elevated apoE levels correlate with impaired cognitive function (Kadish et al 2009). Increased apoE expression resulting from high dietary cholesterol in humans is also associated with an increased incidence of AD (Petanceska et al 2003). Nonhuman primates show an age-related decline in performance on tasks associated with PFC and hippocampal Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Role of disrupted cholesterol metabolism in a transgenic mouse model of AD has been studied, which shows that the dietinduced chronic changes in plasma cholesterol also increase apoE content in the liver and the brain 42 . These findings have been further corroborated by the increased secretion of apoE by glial cells following cholesterol loading, and decreased apoE, following treatments with statins 42 . These data corroborate the findings in the present study that dietary cholesterol up-regulates brain apoE by transcriptional mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Increased generation and secretion of A ␤ leads to the formation of oligomeric and aggregated A ␤ . Chronic increases in serum total cholesterol also increase apoE mRNA levels in brain and increase glial cell and secreted apoE levels (95). Studies in animal models have shown that diet-induced hypercholesterolemia increases A ␤ and apoE concentrations in temporal and frontal cortices, but not in cerebellum, and that these regional increases parallel the amyloid pathology observed in the AD brain (96).…”
Section: Cholesterolmentioning
confidence: 99%